2014
DOI: 10.1038/mi.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived JAML inhibits repair of intestinal epithelial injury during acute inflammation

Abstract: Neutrophil transepithelial migration (TEM) during acute inflammation is associated with mucosal injury. Using models of acute mucosal injury in-vitro and in-vivo, we describe a new mechanism by which neutrophils infiltrating the intestinal mucosa disrupt epithelial homeostasis. We report that junctional adhesion molecule-like protein (JAML) is cleaved from neutrophil surface by zinc-metalloproteases during TEM. Neutrophil-derived soluble JAML bound to the epithelial tight junction protein coxsackie-adenovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 51 publications
(72 reference statements)
2
52
0
Order By: Relevance
“…81 Subsequent studies have revealed that JAML is shed from activated neutrophils during transepithelial migration, and shed ectodomains retain binding to epithelial CAR, resulting in signaling events that inhibit barrier recovery and wound healing. 82 These results appear at odds with other reports of JAML-CAR interactions facilitating T-cellemediated wound healing in the skin of mice. 83 However, in those studies, prorestitutive signals were derived downstream of from T-cell expressed JAML, whereas the inhibitory signals during transepithelial migration of neutrophils were derived downstream of epithelial expressed CAR.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 71%
“…81 Subsequent studies have revealed that JAML is shed from activated neutrophils during transepithelial migration, and shed ectodomains retain binding to epithelial CAR, resulting in signaling events that inhibit barrier recovery and wound healing. 82 These results appear at odds with other reports of JAML-CAR interactions facilitating T-cellemediated wound healing in the skin of mice. 83 However, in those studies, prorestitutive signals were derived downstream of from T-cell expressed JAML, whereas the inhibitory signals during transepithelial migration of neutrophils were derived downstream of epithelial expressed CAR.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 71%
“…Meanwhile, hosts might suffer from damage caused by invading microbes and the immune response (13). For example, neutrophil transepithelial migration during inflammation increases epithelial permeability and tissue damage by altering the barrier function and homeostasis of the epithelium (31). Therefore, it is not surprising that the migration of abundant neutrophils across the epithelium facilitates host-induced tissue damage, which includes organ dysfunction and inflammation-related diseases and even leads to death (17,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, PMN shed JAML during TEM and the binding of soluble JAML to CAR resulted in faulty epithelial resealing and significantly impaired mucosal wound healing. 74 These findings defined CAR as a key regulator of intestinal homeostasis and identified a novel PMN infiltration mechanism that may affect both epithelial barrier and wound healing.…”
Section: Tight Junction Signaling and Function During Pmn Transepithementioning
confidence: 97%
“…74,93,94 Similar to JAM-A, CAR can engage in homophilic interactions 95 ; however, it also binds JAML, a JAM-like protein expressed exclusively on PMNs, monocytes, and gd T-cells, 74,96 with high affinity. While these observations marked the CAR-JAML ligand pair as an attractive candidate for PMN trafficking regulation, a recent study found that inhibiting these interactions only had a minor effect on PMN TEM.…”
Section: Tight Junction Signaling and Function During Pmn Transepithementioning
confidence: 98%
See 1 more Smart Citation